The Hunger games: the impact of hunger on risk preference - Silva, Bernardo Barbosa Machado da (2014)
We often feel hungry and we also often make decisions that involve risk and uncertainty. However, little is known about the influence of the feeling of hunger on risk preference. Previous studies have suggested that hunger is capable of altering people’s attention and perception, but could it also be capable of altering risk preferences? In two experiments, this current study explores the relationship between hunger and risk preference. Visual food-related stimuli are used to manipulate hunger followed by a real gambling task, which assesses risk propensity. The results suggest that hunger may reduce risk-taking in gambling-like situations. Interestingly, the phenomenon seems particularly true among those who are in general more prone to take risks (i.e., male participants).